Factors affecting vitamin D status in different populations in the city of São Paulo, Brazil: the São PAulo vitamin D Evaluation Study (SPADES) - Maeda, Sergio Setsuo (BioMed Central, 2013)
BACKGROUND: Hypovitaminosis D is a common condition among elderly individuals in temperate-climate countries, with a clear seasonal variation on 25 hydroxyvitamin D [(25(OH)D] levels, increasing after summer and decreasing after winter, but there are few data from sunny countries such as Brazil. We aimed to evaluate 25-hydroxyvitamin D concentrations and its determining factors, in individuals in the city of São Paulo belonging to different age groups and presenting different sun exposure habits. METHODS: 591 people were included as follows: 177 were living in institutions (NURSING HOMES, NH, 76.2 ± 9.0 years), 243 were individuals from the community (COMMUNITY DWELLINGS, CD, 79.6 ± 5.3 years), 99 were enrolled in physical activity program designed for the elderly (PHYSICAL ACTIVITY, PA, 67.6 ± 5.4 years) and 72 were young (YOUNG, 23.9 ± 2.8 years). Ionized calcium, PTH, 25(OH)D, creatinine and albumin were evaluated. ANOVA, Mann–Whitney and Kruskal Wallis tests, Pearson Linear Correlation and Multiple Regression were used in the statistical analysis. RESULTS: 25(OH)D mean values during winter for the different groups were 36.1 ± 21.2 nmol/L (NH), 44.1 ± 24.0 nmol/L (CD), 78.9 ± 30.9 nmol/L (PA) and 69.6 ± 26.2 nmol/L (YOUNG) (p < 0.001) while during summer they were 42.1 ± 25.9 nmol/L, 59.1 ± 29.6 nmol/L, 91.6 ± 31.7 nmol/L and 103.6 ± 29.3 nmol/L, respectively (p < 0.001). The equation which predicts PTH values based on 25(OH)D concentration is PTH = 10 + 104.24.e(-(vitD-12.5)/62.36) and the 25(OH)D value above which correlation with PTH is lost is 75.0 nmol/L. In a multiple regression analysis having 25(OH)D concentration as the depending variable, the determining factors were PTH, ionized calcium and month of the year (p < 0.05). CONCLUSIONS: Much lower 25(OH)D values were found for the older individuals when compared to younger individuals. This finding is possibly due to age and habit-related differences in sunlight exposure. The existence of seasonal effects on 25(OH)D concentration throughout the year was evident for all the groups studied, except for the nursing home group. According to our data, PTH values tend to plateau above 75 nmol/L.